Surgical management of third nerve palsy. - Noonan, C P (1995)
AIMS--A surgical technique has been developed in order to obtain ocular alignment in the primary position in patients with third nerve palsy. METHODS--A method for surgically correcting the vertical deviation and the pseudoptosis is described in three patients with longstanding third nerve palsy. By decreasing the ability of the non-involved eye to elevate, a fixation duress was created which eliminated the secondary deviation that characteristically occurs in such patients when the involved eye fixates. As a result of this technique, both eyes in all patients on attempted fixation were under similar duress, therefore requiring equal amounts of stimulation to move into the primary position. When the fixation duress was sufficient, elimination of the hypotropia and ptosis was achieved. Additionally, in order to correct the exotropia, generous recession and resection procedures in the involved eye and recession of the lateral rectus in the noninvolved eye were performed. RESULTS--Between 8 and 10 prism dioptres of esotropia were achieved and maintained in two patients. One patient had 20 prism dioptres of exotropia. Two patients had no residual ptosis and one required an additional anterior levator resection to achieve a satisfactory result. CONCLUSION--Patients with a third nerve palsy and a pseudoptosis may be candidates for this approach.